SITUATIONAL LEADERSHIP DYNAMICS: ITS INFLUENCE ON HUMAN RESOURCE DEVELOPMENT IN THE ENTREPRENEURIAL CONTEXT - Sunarso, Budi (PT. LITERASI SAINS NUSANTARA, 2024)
Entrepreneurship has been acknowledged as one of the primary drivers of economic growth in various countries worldwide. In the era of globalization and increasing competition, entrepreneurship becomes crucial in strengthening a nation's competitiveness. This study aims to examine the dynamics of situational leadership and its influence on human resource development in the context of entrepreneurship. The research method employed in this study is a qualitative literature review using data obtained from Google Scholar for the period from 2009 to 2023. The study findings indicate that situational leadership dynamics have a significant impact on human resource development (HRD) in the context of entrepreneurship. This concept emphasizes the importance of leadership adaptation to various rapidly changing and complex situations. By recognizing individual needs and team dynamics, leaders can facilitate learning, growth, and innovation within the organization.